Cosmic Dance: A technoshamanic journey through consciousness - Simão, Emília (2024)
From archaic contexts to current reconfigurations, the shaman, wrapped in magical-religious lineages, operates as a guiding element, inducer of ecstatic states, and mediator between worlds. Can technology allow these attributes when digital codes and organic webs spin together, fueling cosmological dances and transitions to altered states of consciousness? The project Cosmic Dance, A Tecnhoshamanic Journey through Consciousness, explores the concept of technoshamanism, from which an allusion - possible or metaphorical - to the shamanic facet of technology is proposed.